Аналіз моделі системи управління двомодульної АЕС з реакторами четвертого покоління типу HTR - Маковійчук, Анатолій Анатолійович (Національний технічний університет "Харківський політехнічний інститут", 2018)
Проведено аналіз технологічної частини АЕС з модульним реактором типу HTR. Виявлено основні проблеми дослідження маневреності та стабільної роботи АЕС з модульними реакторами. Створена динамічна модель в середовищі MATLAB/Simulink для АЕС типу HTR-PM з двома реакторними модулями для дослідження основних законів управління реакторними модулями та координації модулів. Отримані результати моделювання підтверджують стабільну роботу мультимодальної АЕС під час поетапного зниження потужності першого та другого модулів.

The analysis of the technological part of the nuclear power plant with a modular reactor of the HTR type was carried out. The main problems of studying the mobility and stable operation of nuclear power plants with modular reactors are revealed. A dynamic model was created in the MATLAB/ Simulink environment for the HTR-PM type nuclear power plant with two reactor modules for studying the basic laws governing reactor modules and coordinating modules. The obtained simulation results confirm the stable operation of the multi-module nuclear power plant during the stage-by-stage reduction of the power of the first and second modules. The high-temperature gas-cooled reactor is a reliable concept for the fourth generation modular reactor, which can be considered as the basic option for further development of the nuclear energy sector of Ukraine.
Analizing of control system model of two-modular nuclear power plant with generation 4 reactors type HTR
Keywords: алгоритм регулювання; динамічне моделювання; control algorithm; dynamic modeling